Release call of Bokermannohyla ibitipoca Caramaschi & Feio, 1990 (Anura, Hylidae) - Pereira, Elvis Almeida; Folly, Henrique; Lacerda, João Victor Andrade; Rebouças, Raoni (Zootaxa, 2019)
Bokermannohyla ibitipoca is a small-sized hylid frog (males reaching up to 43 mm in snout-vent length) of the B. circumdata group (Faivovich et al. 2005). This species was described from the Ibitipoca State Park (Municipality of Lima Duarte) in southern Minas Gerais, at the elevation of 1200 m. Bokermannohyla ibitipoca is restricted to the Mantiqueira Complex area (Caramaschi & Feio, 1990), where it occurs in primary and secondary gallery forests. This species is found on the ground or on the leaf-litter near water and uses permanent streams for calling and reproduction. Here, we quantitatively describe the release call of B. ibitipoca, with comments on similarity to its advertisement call. Although used less frequently than advertisement calls, release calls have been used to diagnose species and infer phylogenetic relationships (Sullivan & Malmos, 1994; Stöck et al. 2000; di Tada et al. 2001; Wogel et al. 2004; Márquez & Eekhout 2006; Oliveira et al. 2012; Sanabria & Quiroga 2012; Grenat & Martino 2013).